Planning and Plotting: A Note on Terminology - Smith, Henry (Review of Economic Studies, 1936)
Journal Article Planning and Plotting: A Note on Terminology Get access Henry Smith Henry Smith Liverpool Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 3, Issue 3, June 1936, Pages 193–200, https://doi.org/10.2307/2967627 Published: 01 June 1936